2023
DOI: 10.3390/antiox12122041
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of Defatted Cherry Seed Residues from Liquor Processing by Matrix Solid-Phase Dispersion Extraction: A Sustainable Strategy for Production of Phenolic-Rich Extracts with Antioxidant Potential

Sandra Rodríguez-Blázquez,
Lorena Fernández-Ávila,
Esther Gómez-Mejía
et al.

Abstract: The integrated valorization of food chain waste is one of the most promising alternatives in the transition to a sustainable bioeconomy. Thus, an efficient solid-phase matrix dispersion extraction method, using experimental factorial design and response surface methodology, has been developed and optimized for the recovery of polyphenols from defatted cherry seeds obtained after cherry liquor manufacture and subsequent fatty acid extraction, evaluating the effect of each processing step on the composition and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…This is attributed to the potential extraction of other hydrophilic components of the seeds during Soxhlet extraction, which enriches the content of defatted seeds. That being so, the lower content of defatted seed in PAFD may be related to its lower content of hydrophilic compounds, such as proteins, sugars, and even polyphenols [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This is attributed to the potential extraction of other hydrophilic components of the seeds during Soxhlet extraction, which enriches the content of defatted seeds. That being so, the lower content of defatted seed in PAFD may be related to its lower content of hydrophilic compounds, such as proteins, sugars, and even polyphenols [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, these results are in line with data found in the literature. The fat content of plum seeds of the variety P. domestica L. extracted by Soxhlet using n -hexane as a solvent usually varies between 30 and 38.7%, w [ 6 , 12 ]. Concerning the effect of processing on oil content, Rodríguez-Blázquez et al [ 12 ] demonstrated that defatted P. avium L. seed residues decreased their content during brandy processing, thereby increasing their oil content.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations